Keanekaragaman dan Potensi Ficus Sebagai Jenis Kerangka untuk Rehabilitasi Hutan dan Lahan di Tahura Profesor Ir. Herman Yohanes, Desa Apren, Kecamatan Amarasi Selatan, Kabupaten Kupang - Daris A. S. Tahun; Astin E. Mau; Maria M. E. Purnama (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
This research was conducted in the Prof. Ir. Herman. Yohanes Community Forest Park (Tahura) Area, in Apren Village, South Amarasi District, Kupang Regency, East Nusa Tenggara, with the results of the study showing that the Ficus genus identified in Apren Village, South Amarasi District, Kupang Regency is 16 types of Ficus out of 19 types of Ficus there are 3 types of Ficus that are not identified, namely Ficus Callophylla, Ficus Caulocarpa and Ficus Fulva. While the 16 types of Ficus identified in Apren Village, South Amarasi District, Kupang Regency are Ficus Ampelas, Ficus Benjamina, Ficus Callosa, Ficus Drupacea, Ficus Hispida, Ficus Microcarpa, Ficus Nervosa subsp. Pubinervis, Ficus Racemosa, Ficus Septica, Ficus Superba, Ficus Tintoria subsp, Gibbosa, Ficus Tintoria subsp. Tintoria, Ficus Varieagata, Ficus Virens, Ficus Virgata and Ficus Wassa Roxb, which are recorded in 5 subgenus namely Urostigma, Pharmacosycea, Sycomorus, Sycidium and Ficus. According to the results of the study above, it can be concluded that the diversity of Ficus species according to the Shannon & Wiener diversity index, 1≤ H’≤3 which indicates moderate diversity. For each type of habitat, the highest species diversity is found in river habitats with H’= 2.7161 and the lowest diversity is found in residential habitats H’= 1.8191.